Earlier Seasonal Onset of Intense Mesoscale Convective Systems in the Congo Basin Since 1999. Issue 24 (19th December 2018) - Taylor, Christopher M.; Fink, Andreas H.; Klein, Cornelia; Parker, Douglas J.; Guichard, Françoise; Harris, Philip P.; Knapp, Kenneth R.
Abstract: Mesoscale convective systems (MCSs) produce some of the most intense rainfall on the planet, and their response to climate variability and change is rather uncertain. Under global warming, increased water vapor is expected to intensify the most extreme rain events and enhance flood frequency. However, MCS dynamics are also sensitive to other atmospheric variables, most notably, wind shear. Here we build on a recent study showing strong MCS intensification in the African Sahel, and examine evidence of similar trends elsewhere in tropical Africa. Using satellite data, we find a remarkable increase post‐1999 in intense MCS frequency over the Congo Basin during the month of February. This earlier onset of the spring rainy season has been accompanied by strong increases in the February meridional temperature gradient and associated wind shear. This supports the hypothesis that contrasts in warming across the continent can drive important decadal‐scale trends in storm intensity. Plain Language Summary: Understanding how storms will change in a warming world is a major scientific challenge and one that has important impacts on society. Changes in the amount of atmospheric water vapor is considered to be the major driver for historical and future trends in intense storms. Here we examine how the intensity of storms over equatorial Africa has evolved since the early 1980s. Building on a previous landmark study over the semiarid Sahel region of North Africa, we identify that substantial storm intensification has taken place over the tropical forests of the Congo Basin, in February, marking the start of the first rainy season. The number of intense storms in that month has jumped by more than 100% since 1999, coinciding with a warming of 2 °C in the more arid parts of North‐Eastern Africa. Episodes of high temperatures over Sudan change the winds and moisture over the Congo Basin, and these factors favor more explosive storms. This provides additional evidence that African storms are sensitive to changes in temperature gradients across the continent and not just atmospheric humidity. These gradients are expected to increase with climate change, likely raising the frequency of flood events. Key Points: Thirty‐five years of satellite data reveal an MCS intensification trend over equatorial Africa in February There is a strong interannual correlation between Congo MCS intensity and temperature over the Eastern Sahel and Sahara Upper‐level wave trains from the extratropics are implicated in Sahelian warm events